15 Month follow up of African children following vaginal cleansing with benzalkonium chloride of their HIV infected mothers during late pregnancy and delivery. Issue 4 (1st August 2002) - Mandelbrot, L; Msellati, P; Meda, N; Leroy, V; Likikouët, R; Van de Perre, P; Dequae-Merchadoux, L; Sylla-Koko, F; Ouangre, A; Ouassa, T; Ramon, R; Gautier-Charpentier, L; et al.
Abstract : Objectives: To study mother to child HIV-1 transmission (MTCT) and infant mortality following benzalkonium chloride (BC) disinfection. Methods: A randomised, double blind phase II placebo controlled trial. Women testing positive for HIV-1 infection in prenatal care units in Abidjan, Côte d'Ivoire, and Bobo-Dioulasso, Burkina Faso, from November 1996 to April 1997 were eligible, with their informed consent. Women self administered daily a vaginal suppository of 1% BC (53) or matched placebo (54) from 36 weeks of pregnancy, plus a single dose during labour. The neonate was bathed with 1% BC solution or placebo within 30 minutes after birth. MTCT rate was assessed based on repeated polymerase chain reaction (PCR) and serology results. For the present analysis, children were followed up to 15 months. Results: A total of 107 women were enrolled. Of 103 eligible liveborn children, 23 were HIV infected, 75 uninfected, and five of indeterminate status. MTCT transmission rate was 24.2% overall (95% confidence interval (CI): 14.3% to 30.4%). On an intent to treat basis, the transmission rate did not differ between the two groups (23.5%, CI 13.8 to 38.5, in the BC group and 24.8%, CI 15.0 to 39.6, in the placebo group at 15 months). Similarly, there was no difference in mortality at 15 months (22.9%, CI 13.7 to 36.9, in the BC group and 16.5%, CI 9.0 to 29.4, in the placebo group). Conclusion: This analysis failed to suggest any benefit of BC disinfection on mother to child HIV transmission or perinatal and infant mortality.